Applied behavior analysis : principles and procedures for modifying behavior - Sarafino, Edward P. , 1940- (Wiley, 2012)
"Sarafino's goal in Principles and Procedures for Modifying Behavior is to create a clear and engaging instrument that describes ways to analyze one's own specific behaviors in terms of the factors that lead to and maintain them and ways to manage those factors to improve the behaviors. The text is based on research, theory, and experiences to explain and provide examples of the concepts and methods of self-management in a comprehensive text. It focuses on topics in applied behavior analysis, behavior modification, behavior therapy, and psychology of learning.Two general topics shaped this text: making the book relative to a variety of fields by describing applications in psychology, education, counseling, nursing, and physical therapy and different academic levels and preparation. Several important objectives guided the content and organization of the text which is designed to cover a large majority of tasks or concepts that the Behavior Analyst Certification Board (www.bacb.com) has identified as the field's essential content and should be mastered by all behavior analysts"